Norborn-2-en-7-ones as physiologically-triggered carbon monoxide-releasing prodrugs. Issue 8 (7th June 2017) - Kueh, Jui Thiang Brian; Stanley, Nathan J.; Hewitt, Russell J.; Woods, Laura M.; Larsen, Lesley; Harrison, Joanne C.; Rennison, David; Brimble, Margaret A.; Sammut, Ivan A.; Larsen, David S.
Abstract : A prodrug strategy for the release of the gasotransmitter carbon monoxide (CO) at physiological pH, based upon 3 a -bromo-norborn-2-en-7-one Diels–Alder cycloadducts has been developed. Abstract : A prodrug strategy for the release of the gasotransmitter CO at physiological pH, based upon 3 a -bromo-norborn-2-en-7-one Diels–Alder cycloadducts of 2-bromomaleimides and 2, 5-dimethyl-3, 4-diphenylcyclopentadienone has been developed. Examples possessing protonated amine and diamine groups showed good water solubility and thermal stability. Half-lives for CO-release in TRIS-sucrose buffer at pH 7.4 ranged from 19 to 75 min at 37 °C and 31 to 32 h at 4 °C. Bioavailability in rats was demonstrated by oral gavage andoCOm-21 showed a dose dependent vasorelaxant effect in pre-contracted rat aortic rings with an EC50 of 1.6 ± 0.9 μM. Increased intracellular CO levels followingoCOm-21 exposure were confirmed using a CO specific fluorescent probe.